2017
DOI: 10.21010/ajtcam.v14i3.23
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Chemical Composition, Antimicrobial, Antioxidant, and Cytotoxic Properties of Essential Oil From Dracocephalum Kotschyi Boiss

Abstract: Background: Dracocephalum kotschyi Boiss is a herb with wide-spread applications. Lorestan traditional healers have applied it for the treatment of rheumatoid diseases and stomach disorders. Materials and methods: Hydrodistillation process was used for essential oil extraction, the extracted essential oil was then analyzed through combination of capillary GC-FID, GC-MS and RI. The in vitro antimicrobial, antioxidant and cytotoxic activities of this essential oil were examined. Results indicate that the essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 28 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…The minimum inhibitory (MIC) and minimum bactericidal (MBC) concentrations were determined by the broth microdilution method in 96-well microtiter plates [25][26][27][28]. Briefly, bacterial strains were cultured overnight at 37 °C on MHB, adjusted to a final density of 8 log CFU/mL, and used to inoculate (1-10) 96-well microliter plates containing serial dilutions of the essential oils (5120-20 μg/mL) on MHB.…”
Section: Minimum Inhibition Concentration (Mic) and Minimal Bactericimentioning
confidence: 99%
“…The minimum inhibitory (MIC) and minimum bactericidal (MBC) concentrations were determined by the broth microdilution method in 96-well microtiter plates [25][26][27][28]. Briefly, bacterial strains were cultured overnight at 37 °C on MHB, adjusted to a final density of 8 log CFU/mL, and used to inoculate (1-10) 96-well microliter plates containing serial dilutions of the essential oils (5120-20 μg/mL) on MHB.…”
Section: Minimum Inhibition Concentration (Mic) and Minimal Bactericimentioning
confidence: 99%
“…The major components were blumenol C (49.7%), β-cedrene (6.1%), limonene (3.8%), α-guaiene (3.3%), cryptone (3.1%), and α-cyperone (2.7%). The EO was tested for its cytotoxic activity against HepG2 and MCF-7 cells, with IC 50 values of 0.072 and 0.188 mg/mL, respectively [46].…”
Section: Origanummentioning
confidence: 99%
“…This however leaves over 70% of the country's provinces. Ashrafi et al [8] observed that D. kotschyi is native in Iran and grows wild in regions lying between 2000 and 3200m altitudes. However, in recent times, D. kotschyi is reported to be an endangered plant in Iran following excessive harvesting, limited distribution areas, and a lack of cultivation and domestication of the D. kotschyi plant [42].…”
Section: Resultsmentioning
confidence: 99%
“…A number of researchers have presented various constituents of D. kotschyi , with the most frequently reported being limonene, luteolin, geranial, apigenin, and calycopterin. A comparison of the main components of D. kotschyi from different provinces is presented in Table 1 [8, 10, 11, 14, 17, 18, 23–25, 31, 39, 44, 45, 48–66]. In spite of some similarities in reported components, there are significant quantitative and qualitative differences between the samples obtained from different locations in Iran.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation